Functional differences between junctional and extrajunctional adrenergic receptor activation in mammalian ventricle - Ajijola, Olujimi A. (American Physiological Society, 2013)
Increased cardiac sympathetic activation worsens dispersion of repolarization and is proarrhythmic. The functional differences between intrinsic nerve stimulation and adrenergic receptor activation remain incompletely understood. This study was undertaken to determine the functional differences between efferent cardiac sympathetic nerve stimulation and direct adrenergic receptor activation in porcine ventricles. Female Yorkshire pigs (n = 13) underwent surgical exposure of the heart and stellate ganglia. A 56-electrode sock was placed over the ventricles to record epicardial electrograms. Animals underwent bilateral sympathetic stimulation (BSS) (n = 8) or norepinephrine (NE) administration (n = 5). Activation recovery intervals (ARIs) were measured at each electrode before and during BSS or NE. The degree of ARI shortening during BSS or NE administration was used as a measure of functional nerve or adrenergic receptor density. During BSS, ARI shortening was nonuniform across the epicardium (F value 9.62, P = 0.003), with ARI shortening greatest in the mid-basal lateral right ventricle and least in the midposterior left ventricle (LV) (mean normalized values: 0.9 ± 0.08 vs. 0.56 ± 0.08; P = 0.03). NE administration resulted in greater ARI shortening in the LV apex than basal segments [0.91 ± 0.04 vs. 0.63 ± 0.05 (averaged basal segments); P = 0.003]. Dispersion of ARIs increased in 50% and 60% of the subjects undergoing BSS and NE, respectively, but decreased in the others. There is nonuniform response to cardiac sympathetic activation of both porcine ventricles, which is not fully explained by adrenergic receptor density. Different pools of adrenergic receptors may mediate the cardiac electrophysiological effects of efferent sympathetic nerve activity and circulating catecholamines.